PWE-120 High rate of false positives for advanced fibrosis when simple non-invasive fibrosis tests are used in older patients (≥ 65 years) with nafld. (22nd June 2015) - Mcpherson, S; Hardy, T; Henderson, E; Allison, M; Ratziu, V; Francque, S; Burt, AD; Day, C; Anstee, QM
Abstract : Introduction: Simple non-invasive fibrosis scores, such as the FIB-4 and NAFLD fibrosis scores (NFS), are now widely used to identify/exclude advanced fibrosis in patients with NAFLD. Use of these scores in primary care provides a simple objective method to identify patients who need further investigation for advanced fibrosis. Few older patients (≥ 65 years) were included in previous studies, but older patients represent a large proportion of patients with NAFLD in the community. The aim of this study was to assess the performance of simple non-invasive fibrosis tests in older patients (≥65 years old) with biopsy-proven NAFLD. Method: Patients with biopsy proven NAFLD were recruited from 4 specialist fatty liver clinics. The diagnostic performance of the AST/ALT ratio, FIB-4 and NFS were assessed using liver biopsy as the standard. Results: From a total of 634 patients, 76 were ≥65 years (mean age 69 ± 3 years, 35% male, 58% diabetic). 60 (79%) of the older patients had steatohepatitis and 30 (39%) had advanced fibrosis (stage 3–4). In older patients the AUROCs for a diagnosis of advanced fibrosis were 0.73, 0.81 and 0.81 for the AST/ALT ratio, FIB-4 and NFS respectively, which was similar to younger patients (0.69, 0.80 and 0.82 respectively). However the specificity for advanced fibrosis using the FIB-4 and NFS was much lower in the older patients than younger patients (FIB-4 35% vs 79%; NFS 20% vs 66%), leading to a high false positive rate. New cut-offs for older patients were derived to improve the specificity to 70% and did not adversely affect the sensitivity (FIB-4 2.0, sensitivity 77%; NFS 0.12, sensitivity 80%). Conclusion: The diagnostic accuracy for advanced fibrosis using the NFS and FIB-4 score was similar in older and younger patients. However, the specificity for advanced fibrosis was low in older patients (≥ 65 years), resulting in a high false positive rate, which may result in patients undergoing unnecessary further investigations. Adoption of our new cut-offs could reduce the proportion of older patients being referred from primary care for further investigation. Disclosure of interest: None Declared.